Evaluating the effect of the accountability audit of natural resources on carbon emissions reduction in China - Xiong, Liyang; Shu, Yiyi; Li, Xuefeng (Frontiers in Environmental Science, 2024)
The Accountability Audit of Natural Resources (AANR) is a major institutional arrangement for advancing the construction of an ecological civilization in China. Based on the panel data of 271 cities in China from 2005 to 2017, this paper investigates the relationship between the AANR and carbon dioxide (CO2) emissions using a multiperiod difference-in-differences (DID) model. The results show that AANR significantly increases the CO2 emissions reduction rate by 0.009 units at the 5% significance level. The results still hold after a series of robustness tests. Given all else being equal, this significant effect is 0.001. Further analyses show that AANR improves pilot cities' CO2 emissions reduction rate mainly by enhancing their green innovation capability. The mediating effect of cities' green technology innovation capability plays a role of 96.00%, while the AANR's direct effect only accounts for 4.00%. The AANR has significantly positive effects of 0.017 and 0.029 for western cities and cities with high fiscal pressure at the 5% and 1% significance levels, respectively. Therefore, strengthening AANR implementation through enhancing the mediating efficiency of cities' green technology innovations, and implementing dynamically differentiated AANR policies in Chinese meso-cities will contribute to the achievement of China's carbon peaking and carbon neutrality targets.